Suppression of PI3K/Akt/mTOR/c-Myc/mtp53 Positive Feedback Loop Induces Cell Cycle Arrest by Dual PI3K/mTOR Inhibitor PQR309 in Endometrial Cancer Cell Lines - Hsin, I-Lun; Shen, Huang-Pin; Chang, Hui-Yi; Ko, Jiunn-Liang; Wang, Po-Hui (Cells (Basel, Switzerland), 2021)
Gene mutations in PIK3CA, PIK3R1, KRAS, PTEN, and PPP2R1A commonly detected in type I endometrial cancer lead to PI3K/Akt/mTOR pathway activation. Bimiralisib (PQR309), an orally bioavailable selective dual inhibitor of PI3K and mTOR, has been studied in preclinical models and clinical trials. The aim of this study is to evaluate the anticancer effect of PQR309 on endometrial cancer cells. PQR309 decreased cell viability in two-dimensional and three-dimensional cell culture models. PQR309 induced G1 cell cycle arrest and little cell death in endometrial cancer cell lines. It decreased CDK6 expression and increased p27 expression. Using the Proteome Profiler Human XL Oncology Array and Western blot assay, the dual inhibitor could inhibit the expressions of c-Myc and mtp53. KJ-Pyr-9, a c-Myc inhibitor, was used to prove the role of c-Myc in endometrial cancer survival and regulating the expression of mtp53. Knockdown of mtp53 lowered cell proliferation, Akt/mTOR pathway activity, and the expressions of c-Myc. mtp53 silence enhanced PQR309-inhibited cell viability, spheroid formation, and the expressions of p-Akt, c-Myc, and CDK6. This is the first study to reveal the novel finding of the PI3K/mTOR dual inhibitor in lowering cell viability by abolishing the PI3K/Akt/mTOR/c-Myc/mtp53 positive feedback loop in endometrial cancer cell lines.